(untitled) (LACCEI, 2024)
Environmental education is one of the topics that promotes sustainability and ecological awareness among people to care for our planet. The management of solid waste consists of the correct segregation of the materials generated by human activity to reduce the harmful effects on public health. Currently, these issues are relevant, due to the pollution generated throughout the world and it is essential to generate aspects of environmental culture in society. For this, a systematic review was carried out with the main objective of knowing the level of education and environmental management on solid waste in Peru in the last 10 years, through research journals found in databases such as Ciencia Latina, Scielo, Dialnet, Researchgate and DOAJ, where only 20 scientific articles were included according to the objective and methodology aligned to the topic. The results obtained were medium-high for urban areas and medium-low for rural areas. In addition, the limitations of the research were the little research study, the English language, and the restricted access to databases. It is concluded that with a good environmental management plan, the state of environmental education in each department of Peru can be improved.